Pengaruh Perilaku Belajar, Kecerdasan Emosional, Dan Pemahaman Hablumminnannas Terhadap Kepribadian Akademik Di Institut Agama Islam Tafaqquh Fiddin Dumai - Windayani Windayani; Khairil Anwar (AL-FIKRA, 2017)
Based on preliminary research results, it is found that students’ academic personality data of Tafaqquh Fiddin Islamic Institution Dumai is low. The low level of students’ academic personality is presumably due to the influence of learning behavior, emotional intelligence, and the understanding of hablumminnannas. Therefore, the purpose of this research is to analyze the influence of learning behavior, emotional intelligence, and understanding of student hablumminnannas at Tafaqquh Fiddin Islamic Religious Institute Dumai. This research is a quantitative research with the sample of 100 students. The data analysis uses multiple regression to answer the research hypothesis by using software SPSS version 21 and Eviews version 7. The results of this analysis show: The significance value of 0.000 which means the existence of a simultaneous positive influence between learning behavior, emotional intelligence, and hablumminnannas understanding of the academic personality, where F = 53.97% with p < 0.05. The result of the influence of learning behavior, emotional intelligence, and understanding of hablumminnannas is equal to 63%. Partially viewed as the highest variable affecting the academic personality is understanding hablumminnannas.